Passional culture : emotion, religion, and society in Southern Spain - Mitchell, Timothy (Timothy J.) (Philadelphia : University of Pennsylvania Press, 1990)
The Holy Week dramas of southern Spain have astounded visitors for centuries. Striking as they are, however, they are only the tip of a cultural iceberg. Casual visitors cannot guess how the cult of the crucified Christ shapes daily behavior and thought patterns. The Passion as lived by Andalusians is closely linked to a penitential ideology that profoundly influences how they feel about life, death, wealth, and poverty. It affects the way men and women see themselves and each other, and has played havoc with Catholic orthodoxy by creating unique institutions and customs. In Passional Culture, Timothy Mitchell explores these cultural factors and shows how they have led to popular stagings of the Passion that are moving, riddled with heresy, and obsessed with authority conflicts. He explains why the image of the Mater Dolorosa has come to overshadow that of Christ himself. With keen analysis as well as anecdotes, illustrations, and popular songs, Mitchell makes fascinating aspects of Spanish civilization available to Americans for the first time -- Book jacket.
Frontmatter -- Contents -- Preface -- Introduction -- 1. Emotion Magic -- 2. The Uses of Pain -- 3. Social Psychology of the Cofradía -- 4. The Passion Retold -- Glossary -- Bibliography -- Index
Includes bibliographical references (pages 185-194 and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
In English.
Keywords: Andalusia (Spain) -- Social life and customs; Andalusia (Spain) -- Religious life and customs; Holy Week -- Spain -- Andalusia; Emotions -- Religious aspects -- Catholic Church; Andalousie (Espagne) -- Mœurs et coutumes; Andalousie (Espagne) -- Vie religieuse; Semaine sainte -- Espagne -- Andalousie; HISTORY -- Europe -- Spain & Portugal; Emotions -- Religious aspects -- Catholic Church; Holy Week; Manners and customs; Spain -- Andalusia; Karwoche; Brauch; Andalusien; Passietijd; Volksgebruiken; Volkscultuur; Rooms-katholicisme.; Andalusia (Spain) -- Religious life and customs; Andalusia (Spain) -- Social life and customs; Emotions -- Religious aspects -- Catholic Church; Holy Week -- Spain -- Andalusia